Granulomatosis with Polyangiitis Localized in the Greater Omentum - Ryuji Komine; Takashi Kobayashi; Hiro Uehara; Keisuke Minamimura; Kazuhiko Mori; Toru Hirata; Atsushi Shimizu; Masaya Mori (Case Reports in Surgery)
Granulomatosis with polyangiitis (GPA) is known as anti-neutrophil cytoplasmic antibody- (ANCA-) associated small vessel vasculitis and typically manifests as pulmonary-renal syndrome, but the disease is not limited to pulmonary or renal systems. The inflammation can involve whole body organs. In addition, the ANCA titer does not always become positive. Here, we describe the case of a 91-year-old man who presented with umbilical pain and fever of unknown origin. Only the increased computed tomography value of the greater omentum suggested intra-abdominal inflammation; however, serological examinations, including the ANCA level, could not reveal the focus or cause of symptoms. Finally, the histopathological examination of specimens surgically excised from the greater omentum demonstrated GPA limited to the greater omentum. This report reminds physicians to consider GPA in the differential diagnosis of acute abdominal pain or fever of unknown origin.